Peningkatan Produktivitas Lahan Pekebun melalui Sertifikasi Kelapa Sawit Berkelanjutan di Indonesia - Rahutomo, Andreas Budi; Karuniasa, Mahawan; Frimawaty, Evi (Analisis Kebijakan Pertanian, 2025)
Indonesian oil palm smallholders own a significant portion of land yet achieve the lowest productivity compared to state and corporate-owned plantations. Meanwhile, increasing productivity is crucial to delink palm oil from deforestation due to the expansion of cultivated land. This research aims to analyse the correlation between Indonesian Sustainable Palm Oil (ISPO) and Roundtable on Sustainable Palm Oil (RSPO) Certification with increasing smallholders’ productivity. First, descriptive statistic analysis was applied to datasets of ISPO and RSPO-certified and non-certified smallholders to compare their productivity. Afterward, a content analysis was done on the certification audit report to assess their compliance with ISPO and RSPO criteria related to land productivity. Results of this study indicated that ISPO and RSPO-certified smallholders have higher average productivity with a difference of 10.52 tonnes of fresh fruit bunches (FFB) per ha or 82% higher than conventional smallholders, in line with good agricultural practices implementation of both certification criteria. This research places the increasing land productivity as a certification’s intrinsic benefit, which provides better incentives than unstable market premium prices. Henceforth, ISPO and RSPO scheme owners need to synergise in accelerating smallholders certification while delinking palm oil from deforestation through increased land productivity.
Keywords: certification benefit; ISPO; land productivity; oil palm smallholders; RSPO